An empirical investigation into the determinants of stock market behaviour in South Africa - Olalere, Durodola Oludamola (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2007)
The argument with regards to whether macro-economic fundamentals determine stock market behaviour is very important because of the roles it plays in an economy. Such roles include: pooling and trading of risks, mobilization of savings, provision of liquidity and allocation of capital. However, the stock market will only perform such roles effectively if the macro-economic environment is conducive. This study examined the behaviour of the All Share Index (ALSI) and market capitalization on the Johannesburg Stock Exchange in response to changes in the domestic and international macro-economic fundamentals such as the consumer price index, rand-dollar real exchange rates, domestic GDP, yield on South African government bonds, yield on United States government bonds and United States GDP. The study used cointegration and error correction techniques proposed by Johansen and Juselius (1990) to test for long run relationship. Two separate models were estimated and results obtained show that the two proxies for the stock market behaviour (All share Index and market capitalization) are true endogenous variables, but react differently to economic fundamentals. The consumer price index has a significant negative impact on the JSE share price index while market capitalization is determined predominantly by the yield on South African government bonds. The exchange rate seems to have had little or no influence on the share price index, but becomes negative and significant in the case of market capitalization. The yield on United States government bonds also produced a strong influence on both the share price index and market capitalization. While it has a negative significant impact on share prices, it produced a positive significant impact on market capitalization. In order to ascertain whether the South African interest rate or the United States interest rate is more important in explaining the share price and market capitalization, each of the variables were estimated in the model separately, the result obtained reveals that the United States interest rate is more important than the domestic interest rate in explaining the share price and market capitalization on the JSE. This implies that investors need to observe the USA interest rate before investing in South African equities. A comparison of the responses of share price index and market capitalization to impulses from the macro-economic variables tested reveals that both proxies elicit a positive response from aggregate output. The share price index responds more significantly to impulses from output growth than the market capitalization, meaning that, as aggregate production increases, the share price index tends to respond positively and quickly. The exchange rate produced mixed result from the two proxies, while it produced a positive response from the market capitalization; an initial positive response was noted in the share price index that immediately turned negative. Another glaring contrast was identified in the response of both proxies to impulses from the United States interest rate. The share price index responded positively while the market capitalization produced a negative response. This finding reveals that the two proxies actually respond differently to macro-economic variables. The variance decomposition of both stock prices and market capitalization reveals that the yield on United States government bonds has a more significant absorption potential than the South African government bonds. However, the absorption process is slower in the case of the market capitalization. The exchange rate has a greater impact on the market capitalization than stock prices. The overall assessment shows that share prices respond faster than market capitalization to macro-economic fundamentals. The study also shows that the increased openness of the South African economy by way of relaxation of the exchange control on capital account transaction has allowed the USA market to play a crucial role in equity prices in South Africa. Three main policy recommendations results from the study. Firstly, if inflation is well monitored, then the local equity market is bound to perform strongly resulting in strong shares earning growth. Secondly, the exchange rate should be made to be less volatile so that long term investment plans across borders can be further enhanced. Thirdly, financial analyst and investors in South Africa need to analyse macro-economic developments in the United States before investing in equities in South Africa.
Keywords: Johannesburg Stock Exchange; Stocks -- Prices -- South Africa; Stock exchanges -- South Africa; Macroeconomics -- South Africa; Interest rates -- South Africa; Foreign exchange rates -- South Africa